Determining the influence of technological factors on the microstructural and rheological parameters of sauces with emulsion structure - Ianushkevych, Oleksandr; Grynchenko, Nataliya; Radchenko, Anna; Smetanska, Iryna; Marynin, Andrii; Hrynchenko, Olha (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is hot sauces with an emulsion structure, namely their microstructural and rheological indicators. The principal task addressed in the study is to identify the possibility of two-cycle heat treatment of sauces with maximum preservation of their properties. This could significantly expand their technological use, in particular, as part of ready-to-eat meals of industrial production. This approach contributes to the justification of the technological use of sauces while simultaneously determining the indicators that are control points in the technological flow of their production. Studies on the microstructure of sauces have demonstrated a bimodal nature of the particle distribution with two pronounced peaks, which are in the range of 2.42–4.03 μm and 31.10–36.30 μm. The SPAN index is in the range of 1.62–1.72, reflecting moderate polydispersity. One- and two-cycle heat treatment of sauces contributes to a decrease in the specific surface area and an increase in the values of the volume-surface diameter of particles, which indicates a change in the microstructural characteristics of sauces. Sauces are structured food systems that demonstrate typical non-Newtonian behavior. During cyclic heat treatment of sauces, there is an increase in viscosity, storage moduli, and losses in the series "freshly made sauce®sauce after 1 heat treatment cycle®sauce after 2 heat treatment cycles". A distinctive feature of the experimental results relates to studying sauces that are consumed hot, which determines additional requirements for their stability. The technological solutions proposed in this paper are aimed at their production in the form of semi-finished products with a high degree of readiness